Thrombotic Thrombocytopenic Purpura Following Honeybee Envenomation: A Case Report - Khalighi, Zahra; Azami, Golnaz; Shafiei, Elham; Sahebi, Ali; Mozafari, Aliashraf (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Background: Thrombotic Thrombocytopenic Purpura (TTP) is a rare and life-threatening disorder characterized by severe thrombocytopenia, microangiopathic hemolytic anemia, fever, renal dysfunction, and neurological deficient. TTP leads to the formation of blood clots in small blood vessels throughout the body. TTP is associated with many risk factors such as pregnancy, HIV, cancer, lupus, and infections. Recently there have been few published case reports of bee sting associated TTP. Methods: A 67-year-old man from a rural area of the Southwest Province of Iran, Ilam, was referred to the academic general hospital because of fever, chills, sweating, vomiting and dizziness following the honeybee sting on his body. Results: this study showed that,multiple co-morbidities including CVD and diabetes, along with coagulation abnormalities after honeybee stings, seriously exacerbated patient hemodynamic status. Conclusion: TTP, as a major complication due to the toxic reaction of a large number of bee stings with underlying diseases in patients, should be given more attention.